Compact and tunable mid-infrared source based on a 2 μm dual-wavelength KTiOPO4 intracavity optical parametric oscillator - 耿优福 谭晓玲 李学金 姚建铨 (Chinese physics B, 2010)
Using a double resonant KTiOPO4 （KTP） intracavity optical parametric oscillator operating at degenerated point of 2 μm, we demonstrate a unique mid-infrared source based on difference frequency generation in GaSe crystal. The output tuning range is 8.42-19.52 μm, and a peak power of 834 W for type-Ⅰ phase matching scheme and 730 W for type-Ⅱ phase matching scheme are achieved. Experimental results show that this oscillator is a good alternative to the generator of a compact and tabletop mid-infrared radiation with a widely tunable range.